Las constelaciones organizacionales como herramientas para resolución de conflictos (2019)
The present monograph initially shows a bibliographic investigation on organizational constellations, where initially a little history is raised about how constellations have evolved over time, through family and structural ones. Next, it demonstrates the application procedure in an organization as the instrument used to manage the diagnosis and approach to the situations presented, ending with the sample that makes the constellations so appropriate with the advantages and disadvantages of making use of them in everyday life.